Pengaruh Brand Image dan Brand Experience terhadap Niat Beli Ulang yang Dimediasi oleh Brand Love - Inaya Sundari Rahmawati; Andriya Risdwiyanto; Nuralam Nuralam (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to examine the influence of brand image, brand experience, and brand love on repurchase intention among McDonald’s consumers in Indonesia. A quantitative approach was employed, using a survey method with questionnaires distributed to 100 respondents. Data were analyzed using Partial Least Squares (PLS) with the assistance of SmartPLS version 4.1.1.2. The results indicate that brand image and brand love have a positive and significant effect on repurchase intention, while brand experience does not show a significant effect. Furthermore, brand love mediates the relationship between brand image and repurchase intention but does not mediate the effect of brand experience. These findings highlight the importance of brand image and emotional attachment in fostering consumer loyalty through repurchase intention.